Masyarakat Adat Dalam Konsepsi Hak Asasi Manusia Di Indonesia Yang Stagnan - Waluyo, Bambang Dwi (Department of International Relations, Universitas Mulawarman, 2023)
The issue of indigenous peoples is becoming an endlessly vital issue in human rights. The rights of indigenous peoples still cannot be accommodated through national policy or international policies. Therefore, this paper identifies the reasons of problems regarding indigenous peoples still cannot be resolved even though there is UNDRIP (United Nations Declaration on the Rights of Indigenous Peoples). Coming out with the question